Global patterns in sandy beach erosion: unraveling the roles of anthropogenic, climatic and morphodynamic factors - Bozzeda, Fabio; Ortega, Leonardo; Costa, Leonardo Lopes; Fanini, Lucia; Barboza, Carlos A. M.; McLachlan, Anton; Defeo, Omar (Frontiers in Marine Science, 2023)
Beach erosion is a complex process influenced by multiple factors operating at different spatial scales. Local (e.g., waves, tides, grain size, beach width and coastal development) and regional (e.g., sea level rise and mean sea level pressure) factors both shape erosion processes. A comprehensive understanding of how these drivers collectively impact sandy beach erosion is needed. To address this on a global-scale we assembled a database with in-situ information on key physical variables from 315 sandy beaches covering a wide morphodynamic range and complemented by satellite data on regional variables. Our results revealed the combined influence of local and regional factors on beach erosion rates. Primary drivers were regional anomalies in mean sea level pressure and variations in mean sea level, and local factors such as tide range, beach slope and width, and Dean’s parameter. By analyzing morphodynamic characteristics, we identified five distinct clusters of sandy beaches ranging from wave-dominated microtidal reflective beaches to tide-modified ultradissipative beaches. This energy dissipation gradient emerged as a critical factor, with erosion rates increasing with beach width and dissipativeness. Our study also highlighted the tangible impact of climate change on beach erosion patterns. Hotspots were identified, where intensification of regional anomalies in mean sea level pressure, increasing onshore winds and warming rates, and rising sea levels synergistically accelerated erosion rates. However, local variables were found to either amplify the effects of regional factors on erosion or enhance a beach’s resistance, mitigating erosive trends initiated by regional drivers. Our analysis showed that more than one-fifth of the analyzed beaches are experiencing intense, extreme, or severe erosion rates, and highlighted the significant role of human activities in explaining erosion trends, particularly in microtidal reflective and intermediate beaches. This underscores the long-term threat of coastal squeeze faced by sandy beaches worldwide and emphasizes the need to consider both local and regional drivers in order to understand erosion processes. Integrating localized measurements with broader satellite observations is required for a comprehensive understanding of the main drivers behind coastal evolution, which in turn is needed to manage and preserve these fragile ecosystems that are at risk.